GENDER DIVERSITY ON BOARDS, WOMEN’S LEADERSHIP AND COMPANY PERFORMANCE (EMPIRICAL STUDY OF FOOD AND BEVERAGE SUB-SECTOR MANUFACTURING COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE IN 2018-2022) - Dwi Apriliani; Sarwenda Biduri (PT. Antis International Publisher, 2024)
General Background: Gender diversity and women's leadership have become critical topics in corporate governance, especially in relation to firm performance. Specific Background: While previous studies have focused on gender diversity’s effects, few have explored the specific influence of gender diversity within the boards of directors and commissioners, particularly in the Indonesian context. Knowledge Gap: The literature lacks clarity on how gender diversity in these distinct leadership roles impacts firm performance in emerging markets like Indonesia. Aims: This study examines the effect of gender diversity on the board of directors, board of commissioners, and women's leadership on firm performance, focusing on manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) from 2018-2022. Results: The findings indicate that gender diversity on the board of directors negatively affects firm performance, while gender diversity on the board of commissioners has a significant positive effect. Female leadership was also found to negatively influence firm performance. Novelty: This study reveals that the impact of gender diversity varies depending on the leadership position, highlighting that while diversity in oversight roles (board of commissioners) can improve performance, diversity in executive roles (board of directors) may have a different effect. Implications: The results suggest that firms and policymakers need to consider the specific context of board roles when promoting gender diversity, as its effects may differ across organizational structures. Additionally, the study underscores the importance of balancing gender diversity initiatives with the decision-making processes within boards to optimize performance outcomes.